Implementation Of The Institutional Level Financial Application System (SAKTI) In Financial Management PSIPKH At BRIN Bogor - Anugrah, Anggita Ramadhiya; Wahyudiono, Bambang; Syafaat, Fitra (Jurnal Mantik, 2025)
Digital transformation in the financial sector is no longer a technological advancement, but a core business strategy. Digital trends have also drastically changed the financial services landscape, pushing institutions to transform their operations and providing a new impetus for seamless digital services. The implementation of a quality information technology system in the government sector will increase efficiency, effectiveness, transparency, and accountability in providing services to the community. Pusat Standardisasi Instrumen Peternakan dan Kesehatan Hewan (PSIPKH) as an institution that plays an important role in maintaining the quality of products and services in the field of animal husbandry and animal health, certainly has a complex financial structure. Funding for this institution generally comes from several sources, including the State Budget (APBN) as a government institution. The research is descriptive qualitative with primary data from the original source of Pusat Standardisasi Instrumen Peternakan dan Kesehatan Hewan and secondary data taken from existing sources. Not only that, researchers use observation, interviews to obtain other data, this study tries to describe how and how effective Direct Transactions (LS) and cash reimbursement (GU) transactions are carried out at the livestock and animal health instrument standardization center. By providing a snapshot of transactions on SAKTI, the results of this study indicate that government agencies are not yet effective in the budget input process on the Sakti application, there are still error problems such as the website on Sakti loading or blanking. This internship aims to understand the mechanism of the Sakti input process in financial management at the Center for Pusat Standardisasi Instrumen Peternakan dan Kesehatan Hewan, the author gains new knowledge, insights and experiences. Especially in financial management in the division of the financial and state-owned goods work team, such as procedures for running the arrangement of official travel files, witnessing the direct payment transaction process (Ls) after making an official trip, inputting data into the application, in addition the author also gains knowledge about the financial process through Ls transactions, cash reimbursement (Gu), and knowing the Government Credit Card (KKP) files